Effect of Electrical Stimulation on Physical and Organoleptic Properties of Muscovy Duck Meat - Harapin Hafid; A Napirah; SM Sarifu; . Rahman; . Inderawati; . Nuraini; . Hasnudi (Jurnal Ilmu Ternak dan Veteriner, 2018)
This research was aimed to study the effect of electrical stimulation period on physical and organoleptic properties of Muscovy duck meat. This research used 20 female Muscovy ducks, 1.5-2 years of age. The ducks were divided into 5 groups treatments for 4 replications. The treatments were period of electrical stimulation: 0, 5, 10, 15, and 20 minutes. The result showed that period of electrical stimulation did not affect (P>0.05) cooking loss but significantly affected (P<0.05) the tenderness, color, flavour, aroma, pH, and juiciness of duck meat. The best treatment was 20 minutes stimulation.